2021
DOI: 10.1186/s12885-021-08330-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of systemic oncological treatments in patients with advanced esophageal or gastric cancers at high risk of dying in the middle and short term: an overview of systematic reviews

Abstract: Background Esophageal and gastric cancers are a significant public health problem worldwide, with most patients presenting with advanced-stage disease and, consequently, poor prognosis. Systemic oncological treatments (SOT) have been widely used over more conservative approaches, such as supportive care. Nevertheless, its effectiveness in this scenario is not sufficiently clear. This paper provides an overview of systematic reviews that assessed the effectiveness of SOT compared with the best s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…therapy, and acknowledged that the quality of evidence is poor [24,25]. In the current prospective multicenter study, we found that adding spray cryotherapy to systemic therapy was associated with an improvement in dysphagia and QoL in patients with inoperative esophageal cancer.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…therapy, and acknowledged that the quality of evidence is poor [24,25]. In the current prospective multicenter study, we found that adding spray cryotherapy to systemic therapy was associated with an improvement in dysphagia and QoL in patients with inoperative esophageal cancer.…”
Section: Discussionmentioning
confidence: 60%
“…▶ Table 3 shows univariable analysis for change in QoL and dysphagia scores across the different categories of predictor variables for a total of 175 cryotherapy treatments. Only tumor ▶ Freeze time, median (range), seconds/cycle 20 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) stage was significantly (statistically but not clinically) associated with an improvement in QoL. None of the evaluated factors were associated with an improvement in dysphagia.…”
Section: Cryotherapy Treatment-level Datamentioning
confidence: 93%
“…Although Akhlaghi et al (2020) reported that receiving palliative chemotherapy was associated with reduced QoL in patients with advanced cancer at the end of life (Akhlaghi et al, 2020), both the Cochrane review by Janmaat et al (2017) and an overview published by our research team (Santero 2021) lacked to detect that palliative chemotherapy and/or targeted therapy decrease QoL (Janmaat et al, 2017;Santero et al, 2021). This probably can be explained by the lack of sensitivity of the included trials to detect changes in most of the qualitative variables.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some patients with advanced EC receive supportive treatmentscommonly referred to as supportive care-to improve symptom control and quality of life (QoL) (Cavanagh et al, 2021), either as a unique treatment or combined with anticancer drugs (Halpern & McCarter, 2019;Harada et al, 2020;Mulazzani et al, 2021). Nonetheless, according to a recent overview of systematic reviews on this topic, the actual bene t of anticancer drugs compared to any supportive approach in patients with advanced EC remains uncertain and has been inadequately summarised (Santero et al, 2021). Thus, the optimal therapy for patients with advanced EC is still debatable.…”
Section: Introductionmentioning
confidence: 99%
“…In China, EC and GC accounted for approximately 50% of global cases and deaths in 2020, imposing a heavy burden on public health ( 1 ). Because of the lack of typical early symptoms, many individuals are initially diagnosed with EC or GC in advanced stages, which may compromise treatment effectiveness and ultimately lead to a dismal prognosis ( 2 ). The overall 5-year survival rates of Chinese EC and GC patients are only 30.3% and 35.1%, respectively ( 3 ).…”
Section: Introductionmentioning
confidence: 99%